Radiotherapy reference dose audit in the United Kingdom by the National Physical Laboratory: 20 years of consistency and improvements. (July 2017) - Thomas, Russell A.S.; Bolt, Matthew A.; Bass, Graham; Nutbrown, Rebecca; Chen, Tao; Nisbet, Andrew; Clark, Catharine H.
Abstract: Background and purpose: Audit is imperative in delivering consistent and safe radiotherapy and the UK has a strong history of radiotherapy audit. The National Physical Laboratory (NPL) has undertaken audit measurements since 1994 and this work examines results from these audits. Materials and methods: This paper reviews audit results from 209 separate beams from 82 on-site visits to National Health Service (NHS) radiotherapy departments conducted between June 1994 and February 2015. Measurements were undertaken following the relevant UK code of practice. The accuracy of the implementation of absorbed dose calibration across the UK is quantified for MV photon, MeV electron and kV X-ray radiotherapy beams. Results: Over the measurement period the standard deviation of MV photon beam output has reduced from 0.8% to 0.4%. The switch from air kerma- to absorbed dose-based electron code of practice contributed to a reduction in the difference of electron beam output of 0.6% ( p  < 0.01). The mean difference in NPL to local measurement for radiation output calibration was less than 0.25% for all beam modalities. Conclusions: The introduction of the 2003 electron code of practice based on absorbed dose to water decreased the difference between absolute dose measurements by the centre and NPL. The use of a single photon code of practice over the period of measurements has contributed to a reduction in measurement variation. Within the clinical setting, on-site audit visits have been shown to identify areas of improvement for determining and implementing absolute dose calibrations.